Saúde bucal e felicidade subjetiva em recrutas do Exército Brasileiro do sul do Brasil - Gazola, Maria Laura Castro Alves Ribeiro (2024)
This study aimed to investigate the socioeconomic, behavioral, clinical and psychosocial factors directly and indirectly associated with subjective happiness in young males in southern Brazil. For this investigation, two military bases were selected in Rio Grande do Sul – 1st Mechanized Cavalry Regiment of Itaqui and 9th Logistics Battalion of Santiago. The sample consisted of recruits carrying out mandatory military service at the aforementioned bases. Data collection took place between 2019 and 2021. Initially, recruits filled out questionnaires to record socioeconomic data (mother's education, family income and participant's education level), behavioral habits (frequency of brushing and flossing), and psychosocial variables, such as sense of coherence (SOC-13 scale), oral health-related quality of life to oral health (Oral Health Impact Profile, in its reduced form consisting of 14 questions [OHIP-14]), and degree of happiness (subjective happiness scale). Then, the volunteers underwent a clinical dental examination to evaluate the gingival bleeding index and the dental caries index (DMFT, number of decayed, missing due to caries or filled permanent teeth). All exams were carried out by a single examiner, trained and calibrated. Path analysis was used to test the direct and indirect paths linking socioeconomic, behavioral, clinical and psychosocial factors to subjective happiness in the study sample. The final sample was composed of 499 recruits. Thus, high levels of sense of coherence were directly linked to greater happiness (β 0.49, p<0.001), while higher OHIP-14 scores, indicating poorer OHRQoL, were directly linked to a lower degree of happiness (β -0.09, p<0.05). When indirect effects were analyzed, untreated caries was indirectly linked to a lower degree of happiness (β -0.03, p<0.05), via oral health-relate quality of life. In conclusion, psychosocial and clinical factors were linked to happiness among recruits from the Brazilian Army from southern Brazil.